All-optical wavelength conversion based on cross-phase modulation (XPM) in a single-mode fiber and a Mach-Zehnder interferometer - Sarker, B.C.; Yoshino, T.; Majumder, S.P. (2002)
An all-optical wavelength converter based on cross-phase modulation in a single-mode fiber (SMF) and a Mach-Zehnder interferometer followed by a Fabry-Perot filter is analyzed. The performance results evaluated at a bit rate of 10 Gb/s with normal and dispersion-shifted fiber (DSF) with optical filtering show that wavelength conversion is possible,without significant reduction in conversion efficiency over a wavelength separation of approximately 10 nm between the input pump-and-probe signals. For pump-and-probe input powers of 10 mW each, the output converted power is found to be -6.5 dBm for normal fiber corresponding to zero wavelength separation and the corresponding output power for wavelength separation of 2 nm is -11 dBm. It is also found that DSF converter provides higher efficiency and output power compared to conventional SMF.